An Exploration of Factors that Influence Customers' Perceptions in the Acceptance of Yield Management Practices within the Hotel Sector - Nguyen, Uyen Hong (International Conference on Tourism Research, 2018)
This study explores the key factors that influence customers' perception of yield management (YM) practices acceptance as well as examining the major drivers that affect customer's behaviours while they engage with YM practices' information. Therefore, the findings of the study may help firms identify the most effective methods for imparting information of the YM practices to customers within the context of hotel industry. Primary research was conducted by means of in-depth semi-structured interviews. Findings reveal that there are several factors that influence customers' perceptions in the acceptance of YM practices. Mainly, price fairness, YM information and other factors (such as culture, gender and education) were all mentioned frequently by the research subjects. In addition, this study notes that customers have negative perceptions of YM practices through the YM information presentation of the firms tend to behave negatively toward the firms that use YM in their strategy of management. However, customers have positive perceptions of the YM practices through the YM information presentation of the firms, adding other actions that firms prepare to enhance the fairness of customers' perceptions, customers are likely to satisfy and potentially have intention to repurchase. Finally, through the analysis of the data, this study has also identified two-way communication which customers are involving and engaging in the process of providing YM practices information to customers, both in online and offline modes. The study demonstrates that customers' feedback and comments are valuable for firms to continuously improve the quality of their information presentation as well as increasing the acceptance levels of YM practices amongst customers.